Estimation of methane emission from Piyungan landfill using IPCC method - Yuli Pratiwi; Paramita Dwi Sukmawati; Fisher Inco Rande Bunga (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2023)
One of the greenhouse gases that causes climate change is the emission of methane (CH4) produced by landfills. The methane comes from the anaerobic decomposition of organic matter in the waste at the landfill. The purpose of this study is to estimate methane emissions at the Piyungan landfill, Bantul, Yogyakarta, from 2021 to 2025 using IPCC method. No similar work has been conducted so far, especially in the Piyungan landfill. The result shows that methane emissions produced at the Piyungan landfill in 2021 is 544.05 tons with a total waste generation of 549.49 tons/year and is dominated by 88% organic waste. Meanwhile from 20,786 tons of waste generated in 2025, the methane emissions are estimated to be 573.85 tons. To minimize the methane emission from Piyungan landfill, it is recommended mitigation and adaptation efforts, i.e., the 3R method (reduce, reuse, recycle), the composting of organic waste, the addition of gas ventilation pipes. The methane gas from the Piyungan landfill should be explored as alternative energy fuel in future work.